Growing media and biofertilizer for Nephrolepis cordifolia (L.) K. Presl. in vertical garden system - Chanchal Gireesh S; I., Priyakumari; Rafeekher M.; Reshmi C. R.; Manju R. V. (Journal of Tropical Agriculture, 2025)
Vertical gardens expand green spaces in urban environments and fulfill various functional roles such as reducing sound and heat, enhancing energy efficiency, improving air quality, mitigating heat islands, optimizing location utilization, creating agricultural spaces, fostering aesthetic appeal, and positively influencing human psychology. Nephrolepis cordifolia (L.) K. Presl., commonly known as fishbone fern/ tuberous sword fern/ ladder fern is predominantly used in vertical gardens. Responses of this fern to five different growing media were analysed by the corresponding growth parameters recorded during the study. The results indicated that the plants grown in medium having coirpith: vermiculite: perlite: vermicompost in the ratio of 1:0.5:0.5:1, recorded better growth performance. Different growth parameters such as plant spread, plant height, number of leaves per plant, number of fronds, total biomass production and total chlorophyll content recorded significantly higher values than those compared to the respective controls. Furthermore, the application of biofertilizer VAM @ 3g/ pot of size 15 x15x 12 cm3 , provided an effective organic source of nutrients for enhanced plant growth under vertical system.